Study Of Chick Embryo Vaccination Against Newcastle And Newcastle With Gumboro: Abdel Ameer H.Zahid , Nawal Salih Jafer , Anton S.AL- Bana - Zahid, Abdel Ameer H. (The Iraqi Journal of Veterinary Medicine, 2005)
This study is considered the first trail study in our country to apply In ovo-vaccination to immunize chicks against avian viral diseases. This method was conducted by using 150 chick embryos classified into three equal groups (50 embryo each group). The first group was inoculated with Newcastle disease virus-NDV (B1-strain). Second group was vaccineted with NDV. and GV( Gambaro virus). All vaccinated groups were inoculated in the amniotic sac, thethird group (control group) was inoculated with sterile phosphate buffered saline. Result should the both vaccine did not reveal any negative effect on the percentage of hatchability and liaviability of the vaccinated chicks.Hemagglutination inhibition (HI) , ELISA and challenge test were used to evaluate the level of immunity in chicks vaccinated with (NDV.) alone and (GV.) & (NDV.) double vaccine beside the control group chicks. The result revealed in spite of lower level of mean antibody titer of HI and ELISA in age of 28 days the two vaccinated group were resistant to challenge with virulent NDV. with 60% mortality rate in the control group.